(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Seenfrom a perspective whichis vigilant to multiple manifestations of symbolic violence, the building of literary canons studied at school and disseminated through institutions, thearts and mass media provides a significant field for examination. In the case of Argentina, from the gauchesco genre a way of viewing the gender positionings within the national community was outlined and the molding of subjectivities influenced. The literary corpus we studied (Ema, la cautiva and El vestido rosa by Cesar Aira, and Las aventuras de la China Iron by Gabriela Cabezón Cámara) interact with this strong expository position, the gauchesca position (heart of the national canon), in order to generate fictional diversions that disrupt the binary logic of the gauchesco genre.